PENGARUH BADAN USAHA MILIK DESA (BUMDES) DAN PROFESIONALISME PENGELOLAAN ASET DESA TERHADAP PENDAPATAN ASLI DESA WUNLAH KECAMATAN WUARLABOBAR KABUPATEN KEPULAUAN TANIMBAR PROVINSI MALUKU - Hermina Bafa; Teguh Erawati; Anita Primastiwi (INVOICE : JURNAL ILMU AKUNTANSI, 2021)
This study aims to prove the influence of village-owned enterprises and the professionalism of village asset management on the original income of the Wunlah Village, Wuarlabobar District. This study uses a quantitative descriptive method with primary data using a questionnaire. This study took samples of village officials, village-owned business entities, village asset managers and the community who actively participated in management. Sampling technique using purposive Sampling. Data collection was done by distributing questionnaires via google form. The number of questionnaires that were processed were 50 questionnaires. Data were analyzed using multiple linear regression analysis. The results of this study indicate that village-owned enterprises and village asset management professionalism have a positive effect on the original income of the Wunlah village, Wuarlabobar sub-district, Tanimbar Islands regency. Keywords: BUMDes, village asset management professionalism, village original income.